2015
DOI: 10.16965/ijar.2015.116
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Shape of Coronoid Process in Dry Mandible of Maharashtra Population

Abstract: Background: Knowledge about the morphological shapes of the coronoid process is useful for the maxillofacial surgeon. The Coronoid process can be easily harvested as a donor bone. It is also helpful in determining buccal vestibule during denture fabrication.Aim of the study: To find out the variation in shape of coronoid process and the intercoronoid distance in dry mandible of Maharashtra region. Material and Methods:One hundred and fifty seven (male 84 and female 73) dry mandible of Maharashtra region were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
3
5
1
Order By: Relevance
“…The most common shape of the coronoid process detected was triangular followed by round with male predominancy seen maximum in the age range of 30-40 years in the population of Bengaluru which is in accordance with Column totals 300 300 600 the studies conducted by Sahithi et al in the South Indian population [7] and Shakya et al, [9] Sudha et al, [13] and Pradhan et al [14] among the South Indian populations. Our comment regarding the shape of coronoid population was totally opposing to the studies conducted by Tapas et al [12] among the North Indian population and Kadam et al [15] among the West Indian population where according to them hook/beak shape to be common followed by the triangular shape. Prajapati et al [16] had conducted a study using dry mandibles and the results showed that triangular coronoid processes were common followed by the round and the hook shapes.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common shape of the coronoid process detected was triangular followed by round with male predominancy seen maximum in the age range of 30-40 years in the population of Bengaluru which is in accordance with Column totals 300 300 600 the studies conducted by Sahithi et al in the South Indian population [7] and Shakya et al, [9] Sudha et al, [13] and Pradhan et al [14] among the South Indian populations. Our comment regarding the shape of coronoid population was totally opposing to the studies conducted by Tapas et al [12] among the North Indian population and Kadam et al [15] among the West Indian population where according to them hook/beak shape to be common followed by the triangular shape. Prajapati et al [16] had conducted a study using dry mandibles and the results showed that triangular coronoid processes were common followed by the round and the hook shapes.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the mean of the inter coronoid distance was 9.01cm, 8.96cm and 9.08 in mandibles showing triangular, rounded and hooked coronoid processes respectively. Our findings coincides with previous studies 18,19 .…”
Section: Fig 2: Showing Hooked Coronoid Processsupporting
confidence: 94%
“…Mean intercoronoid distance among males was found to be 9.2000 and 9.100 in females. 4 Sudha et al also found that shapes of coronoid process were triangular (60.8%), rounded (14%) and hook (25.6%) in their study. Hook shape was found bilaterally in 28.8 %.…”
Section: Discussionmentioning
confidence: 63%
“…2 Many researchers have studied the morphology of coronoid process and have found varying shapes. [3][4][5][6][7][8][9][10][11][12][13] Similar study has not been done in this area. Hence, this study was conducted which will be useful to maxillofacial surgeons, forensic scientists and anthropologists.…”
Section: Introductionmentioning
confidence: 99%